Análise da variabilidade da intensidade do campo elétrico na faixa de 566 a 572 MHz na cidade de Uberlândia. - Santos, Tiago Nunes (2021)
The advancement of civil construction in Brazil, which has been occurring for some years, has had an impact on the modification of urban profiles in cities. As a result of this change, the number of obstacles between the transmitting station and the receiver gradually increased. Consequently, the way that the intensity of the electric field spreads in the urban region is also affected. Therefore, it is necessary to analyze the variability of the intensity of the electric field in the city of Uberlândia, in order to identify the behavior of the regions. This analysis was performed from the collection of electric field samples in several regions. A detailed study of each region was done using the measured samples, using statistical analysis and comparisons of the samples with the free space, hata, ITU-R P.1546 and RNA propagation models. Thus, a correlation of the regions in the city of Uberlândia was identified. The results achieved indicated that the analyzed regions are statistically distinct from each other. In addition, it was found that the urban profile drastically affected the behavior of the electric field.